2015
DOI: 10.11648/j.ajns.20150404.17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Planned Sexual Harassment Protective Program on Feeling of Safety and Self Confidence among Adolescent Girls

Abstract: Abstract:Background: Sexual harassment is a widespread phenomenon among adolescents. Its emergence is correlated to biological development; this behavior is neither normative nor socially appropriate given the negative impact on victims and its association with other aggressive and violent behavior. Enhancing adolescents' self-confidence is helpful in empowering then to feel safe and protected against this antisocial phenomenon. Aim: is to assess the impact of a planned sexual harassment protective program on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…This finding goes in the same line with that of the study conducted by Younis et al (2015), whose study, on the impact of a planned sexual harassment protective program on feeling of safety and self confidence among adolescent girls, showed that, there was highly statistically significant difference between pre and post educational program regarding having enough knowledge to increase their selfconfidence and to feel safe in facing sexual harassment at any time.…”
Section: Discussionsupporting
confidence: 86%
“…This finding goes in the same line with that of the study conducted by Younis et al (2015), whose study, on the impact of a planned sexual harassment protective program on feeling of safety and self confidence among adolescent girls, showed that, there was highly statistically significant difference between pre and post educational program regarding having enough knowledge to increase their selfconfidence and to feel safe in facing sexual harassment at any time.…”
Section: Discussionsupporting
confidence: 86%